The impact of temperature dependent electrical conductivity in radiofrequency ablation treatment planning. (September 2016) - Saroglou, Ioannis; Samaras, Theodoros
Abstract : Introduction: Radiofrequency ablation (RFA) for cancer therapy is usually performed under a medical imaging modality to evaluate tissue necrosis, albeit with some limitations. In recent years, the advancements in computational resources and their wide availability have rendered individualized treatment planning for RFA feasible. However, this approach involves several limitations and approximations, as well. Purpose: In the current study we aim at elucidating the importance of assuming a temperature dependence for the electrical conductivity and its effect in the predicted final temperature distribution and necrotic volume. Materials and methods: The simulated model is a two-compartmental one, which assumes different electrical conductivity in the spherical tumor and the surrounding healthy tissue. A single electrode is entered inside the tumor (monopolar technique). The Laplace and the Pennes bioheat-transfer equations are solved numerically with the finite difference method coded in C, after applying the appropriate boundary conditions. It is assumed that the electrical conductivity in both compartments changes with temperature. Results: The calculated temperature rise and necrosis volume (as assessed by CEM43 °C above a threshold) change considerably when the electrical conductivity varies with temperature. In fact, various formulations for this temperature dependence have been suggested and they can result in differences larger than 15% in the treatment outcome indicators. Conclusion: Currently, it is possible to achieve individualized treatment planning for RFA. However, there is scarce information from the literature on the changes of tissue properties at ablative temperatures, which could lead to more accurate predictions of the treatment outcome.